2017
DOI: 10.1128/jvi.00575-17
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of Vaccinia Virus NF-κB Inhibitor Proteins A52, B15, and K7 in the Immune Response

Abstract: Poxviruses use a complex strategy to escape immune control, by expressing immunomodulatory proteins that could limit their use as vaccine vectors. To test the role of poxvirus NF-B pathway inhibitors A52, B15, and K7 in immunity, we deleted their genes in an NYVAC (New York vaccinia virus) strain that expresses HIV-1 clade C antigens. After infection of mice, ablation of the A52R, B15R, and K7R genes increased dendritic cell, natural killer cell, and neutrophil migration as well as chemokine/cytokine expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 54 publications
(55 reference statements)
2
28
0
5
Order By: Relevance
“…Results showed that the DNA-B/MVA-B ∆A40R immunization group presented significantly enhanced magnitude of the overall adaptive and memory HIV-1-specific CD4+ and CD8+ T cells expressing CD107a, IFN-γ, TNF-α, and/or IL-2 compared to DNA-B/MVA-B. These results further suggest the immunosuppressive role of MVA A40 protein, as deletions of well-known immunosuppressive VACV genes from MVA or NYVAC vectors expressing HIV-1 antigens have produced similar results [18,20,21,23,[69][70][71][74][75][76][77][78]. Furthermore, both immunization groups elicited an adaptive and memory HIV-1-specific T-cell immune response with a similar polyfunctional profile, and mainly TEM and to a lesser extent TE phenotypes.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Results showed that the DNA-B/MVA-B ∆A40R immunization group presented significantly enhanced magnitude of the overall adaptive and memory HIV-1-specific CD4+ and CD8+ T cells expressing CD107a, IFN-γ, TNF-α, and/or IL-2 compared to DNA-B/MVA-B. These results further suggest the immunosuppressive role of MVA A40 protein, as deletions of well-known immunosuppressive VACV genes from MVA or NYVAC vectors expressing HIV-1 antigens have produced similar results [18,20,21,23,[69][70][71][74][75][76][77][78]. Furthermore, both immunization groups elicited an adaptive and memory HIV-1-specific T-cell immune response with a similar polyfunctional profile, and mainly TEM and to a lesser extent TE phenotypes.…”
Section: Discussionsupporting
confidence: 57%
“…Due to the lack of detection (using Western blot or immunofluorescence assays) of A40 protein when expressed from its natural locus in MVA or MVA-B viruses, we decided to reintroduce the MVA A40R gene into the HA locus of the MVA-B ∆A40R under the control of a stronger sE/L viral promoter. A similar strategy was used previously to generate NYVAC-based revertant viruses, which allowed us to demonstrate the important role of NFκB activation by VACV in enhancing neutrophil migration and HIV-1-specific T-cell responses [77,78]. Moreover, it has been reported that insertion of heterologous genes into the MVA HA locus does not affect the expression of neighboring MVA genes and the recombinant viruses generated are functional, indicating that the HA gene region is a suitable insertion site [89].…”
Section: Discussionmentioning
confidence: 89%
“…9). It should be noticed that the VV-encoded proteins A52, B15, and K7 are inhibitors of NF-kB and known to suppress chemokine/cytokine expression from immune cells 43 . Ad-and SFV4-mediated DC activation is immune stimulating as assessed by release of IFN-γ from model antigen-specific CD8 + T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Многочисленные работы, посвященные делеции (удалению) генов иммуномодулирующих факторов VACV, позволили выявить некоторые вирусные гены, инактивация которых наряду с аттенуацией вируса приводит к увеличению его иммуногенности [43][44][45][46][47][48][49][50][51][52][53]. Как видим из данных, приведенных в табл.…”
Section: увеличение иммуногенности аттенуированной противооспенной ваunclassified